CSPAP Professional Preparation and Research Initiatives at the University of South Carolina. Issue 2 (12th February 2017) - Webster, Collin
Abstract : Several comprehensive school physical activity program (CSPAP) professional preparation and research initiatives are underway in the Department of Physical Education and Athletic Training at the University of South Carolina. The CSPAP learning experiences have been mostly integrated into existing courses to help candidates in physical education teaching, classroom teaching and teacher education to develop skills, knowledge and dispositions to lead CSPAPs. Physical education teacher candidates plan, implement and evaluate school- and community-based physical activity-promotion strategies spanning all CSPAP components. Classroom teacher candidates learn to integrate movement in academic classroom settings and advocate for CSPAPs. Doctoral students training to become physical education teacher educators or researchers teach and supervise teacher candidates, evaluate candidates' CSPAP work, and collaborate with faculty on interdisciplinary CSPAP research. These initiatives reflect progress, but they lack a sustained, sequential and systematic approach. Future efforts must focus on gaining the support of all faculty to pursue CSPAP preparation and research that strike a balance between traditional and emerging professional roles and responsibilities in the field.